EKSPLORASI KEARIFAN LOKAL DALAM SASTRA LISAN MASYARAKAT SAMBAS UNTUK PENGUATAN LITERASI - Indriyana Uli; Lizawati (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the forms of oral literature containing local wisdom that are still preserved within the Sambas community and to examine their role in strengthening literacy in schools. The research employed a qualitative descriptive method with an exploratory approach. The data sources consisted of oral traditions of the Sambas Malay community that are still practiced in social, cultural, and religious activities. Data were collected through observation, interviews, and documentation, and were analyzed using an interactive analysis model involving data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, prolonged engagement, and reference adequacy. The findings reveal seventeen forms of oral literature containing local wisdom, namely miare, bepallam, mulang-mulangkan, ngamping, bepappas, besiak, antar ajong, antar pinang, antar pakatan, besaprah, besurong, belalek, tuang minyak, mandek belulus, serakalan, saroan or panggelan, and bemeteng. These traditions embody religious values, mutual cooperation, responsibility, social solidarity, respect for customs, and cultural preservation. Such values are highly relevant to the development of smart literacy and character education in schools, as they can be integrated into local wisdom-based learning. The utilization of oral literature as a learning resource not only enriches students’ cultural knowledge but also fosters awareness of preserving local cultural heritage as part of national identity.